2018
DOI: 10.15438/rr.7.4.195
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Lip Liner Positions Improving Stability in Total Hip Arthroplasty – An Experimental Study

Abstract: Background: The use of elevated lip polyethylene liners with the acetabular component is relatively common in Total Hip Arthroplasty (THA). Elevated lip liners increase stability of the THA by increasing the jump distance in one direction. However, the elevated lip, conversely, also reduces the primary arc in the opposite direction and leads to early impingement of the neck on the elevated lip, potentially causing instability.The aim of the present study is to determine the total range of motion of the femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Additionally, impingement limits the ROM and is a common cause of postoperative instability [47,65]. ROM analyses have raised much attention from the research community using experimental [24][25][26][27][28][29] and numerical methods [21,30,43,44,[46][47][48][49][50]. However, to the best of our knowledge, there is no approach published to assess ROM after THR in surgery planning without applying additional radiation to the patient; for example, by CT scanning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, impingement limits the ROM and is a common cause of postoperative instability [47,65]. ROM analyses have raised much attention from the research community using experimental [24][25][26][27][28][29] and numerical methods [21,30,43,44,[46][47][48][49][50]. However, to the best of our knowledge, there is no approach published to assess ROM after THR in surgery planning without applying additional radiation to the patient; for example, by CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the occurrence of impingement is manually assessed by an orthopedic surgeon, by intraoperatively imposing specific motion patterns while the impingement is detected [23]. To analyze the maximum ROM of different implant designs, several experimental [24][25][26][27][28][29] and computational studies [13,18,20,21,23,[30][31][32][33][34][35][36][37][38], using computer-aided design (CAD), finite element analyses, or multibody simulations, have been conducted. Previous studies described the effect of the orientation of the acetabular cup, prosthetic head size on the impingement, and risk of dislocation [21,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Lateral approach THAs do not seem to benefit from lipped PE liners. Further studies are needed to examine the effects of lip position on revision for instability, with some biomechanical 25 and intraoperative 26 studies suggesting the posteroinferior quadrant to confer better stability. Additionally, studies are needed to determine if a true difference exists between 10° and 15° liners, and whether the benefits of lipped liners persist into longer-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“… 29 The effect of the position of the asymmetric part of the liner (lip) can have a marked effect on the range of motion prior to dislocation as revealed in in vivo and ex vivo studies. 12 , 27 , 30 The association between increased impingement in elevated rim liners and reduced prosthetic joint survival has not been proven. Cobb et al 17 analyzed their institutional database and reported no increase in the risk of revision due to loosening of the acetabular or femoral components when elevated rim liners were used.…”
Section: Discussionmentioning
confidence: 99%